Handbook of Maintenance Management and Engineering - Ben-Daya, Mohamed; Duffuaa, Salih O.; Raouf, Abdul; Knezevic, Jezdimir; Ait-Kadi, Daoud (Springer London : Imprint: Springer, 2009)
The Handbook of Maintenance Management and Engineering covers a wide range of topics in maintenance management and engineering. It includes extensive references to the theoretical foundations, recent research and future directions of this important subject. Using applications and examples which reflect the growing importance of maintenance, this book presents readers with an inter-disciplinary perspective on topical issues which affect any organization engaged in manufacturing, process, or service industry, no matter how large or small. Contributors to the book are maintenance experts with both academic and industrial backgrounds, who are able to offer a comprehensive analysis of the subject matter, including both quantitative treatment and discussion of management issues. The Handbook of Maintenance Management and Engineering features both fundamental and applied works from across the whole maintenance spectrum. It will provide professionals with the solutions and management skills needed to evaluate and to continuously improve maintenance systems. This handbook will also be an invaluable resource for researchers and graduate students working in this area.